Challenges associated with the incorporation of digital radiography into a picture archival and communication system...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Siegel EL; Reiner BI (Journal of Digital Imaging)
Digital radiography (DR) has recently emerged as an attractive alternative to computed radiography (CR) for the acquisition of general radiographic studies in a digital environment. It offers the possibility of improved spatial and contrast resolution, decreased radiation dose due to improved efficiency of detection of x-ray photons, and perhaps most importantly, holds out the promise of increased technologist productivity. To achieve maximum efficiency, DR must be completely integrated into existing information systems, including the hospital and radiology information systems (HIS/RIS) and, when present, the picture archival and communication system (PACS). The early experience with the integration of DR at the Baltimore Veterans Affairs Medical Center (VAMC) has identified several challenges that exist to the successful integration of DR. DR has only recently been defined as a separate Digital Imaging and Communications in Medicine (DICOM) modality and images obtained will, at first, be listed under the category of CR. Matrix sizes with some DR products on the market exceed the current size limitations of some PACS. The patient throughput may be substantially greater with DR than with CR, and this in combination with the larger size of image files may result in greater demands for network and computer performance in the process of communication with the HIS/RIS and PACS. Additionally, in a hybrid department using both CR and DR, new rules must be defined for prefetching and display of general radiographic studies to permit these examinations to be retrieved and compared together. Advanced features that are planned for DR systems, such as dual-energy subtraction, tomosynthesis, and temporal subtraction, will likely require additional workstation tools beyond those currently available for CR. Copyright (c) 1999 by W.B. Saunders Company